Legal Compliance On The Road As The Effort To Overcome Jakarta’s Traffic Congestion - Elfrida Ratnawati Gultom (Faculty of Law, Universitas Jenderal Soedirman, 2019)
Traffic discipline is an important attitude. Road drivers need to be accustomed to it if they want to reach their destination safely. Drivers need to be disciplined regarding regulation. Jakarta is a densely populated city with the problem of traffic congestion due to its road users who do not comply with regulations. Why are the people of Jakarta not discipline in traffic? What is the solution to make them obey traffic rules? These are main problems discussed in this paper. The research used the normative method, analyzed descriptively, used primary data which was supported by secondary data, and processed qualitatively. Jakarta people are not disciplined in traffic because there is no awareness about the importance of traffic order. As solutions, theremust be a strict law enforcement on the road, and officers must keep providing information to the public on the importance of traffic order. There must be sanction as a deterrent effect for those who are not disciplined in traffic.Keywords: legal compliance; law enforcement; traffic order.